Development and function of chicken XCR1+ conventional dendritic cells - Wu, Zhiguang; Shih, Barbara; Macdonald, Joni; Meunier, Dominique; Hogan, Kris; Chintoan-Uta, Cosmin; Gilhooley, Hazel; Hu, Tuanjun; Beltran, Mariana; Henderson, Neil C.; Sang, Helen M.; Stevens, Mark P.; et al. (Frontiers in Immunology, 2023)
Conventional dendritic cells (cDCs) are antigen-presenting cells (APCs) that play a central role in linking innate and adaptive immunity. cDCs have been well described in a number of different mammalian species, but remain poorly characterised in the chicken. In this study, we use previously described chicken cDC specific reagents, a novel gene-edited chicken line and single-cell RNA sequencing (scRNAseq) to characterise chicken splenic cDCs. In contrast to mammals, scRNAseq analysis indicates that the chicken spleen contains a single, chemokine receptor XCR1 expressing, cDC subset. By sexual maturity the XCR1 + cDC population is the most abundant mononuclear phagocyte cell subset in the chicken spleen. scRNAseq analysis revealed substantial heterogeneity within the chicken splenic XCR1 + cDC population.Immature MHC class II (MHCII) LOW XCR1 + cDCs expressed a range of viral resistance genes.Maturation to MHCII HIGH XCR1 + cDCs was associated with reduced expression of anti-viral gene expression and increased expression of genes related to antigen presentation via the MHCII and cross-presentation pathways. To visualise and transiently ablate chicken XCR1 + cDCs in situ, we generated XCR1-iCaspase9-RFP chickens using a CRISPR-Cas9 knockin transgenesis approach to precisely edit the XCR1 locus, replacing the XCR1 coding region with in which genes for a fluorescent protein (, TagRFP), and inducible Caspase 9.